Acetylshikonin is a novel non‐selective cytochrome P450 inhibitor. (6th November 2017) - Shon, Jong Cheol; Phuc, Nguyen Minh; Kim, Won Cheol; Heo, Jae Kyung; Wu, Zhexue; Lee, Hyunyoung; Liu, Kwang‐Hyeon
Abstract: Acetylshikonin is a biologically active compound with anti‐cancer and anti‐inflammatory activity, which is isolated from the roots of Lithospermum erythrorhizoma . An inhibitory effect of acetylshikonin against CYP2J2 activity was discovered recently. Based on this result, this study was expanded to evaluate the inhibitory effects of acetylshikonin against nine different cytochrome P450 (P450) isoforms in human liver microsomes (HLMs) using substrate cocktails incubation assay. Acetylshikonin showed a strong inhibitory effect against all P450s tested with IC50 values of 1.4–4.0 μm . Pre‐incubation of acetylshikonin with HLMs and NADPH did not alter the inhibition potency, indicating that acetylshikonin is not a mechanism‐based inhibitor. SKF‐525A, a widely used non‐specific P450 inhibitor, had no inhibitory activity against CYP1A2, 2A6, 2E1 and 2J2, while it showed an inhibitory effect against CYP2B6, CYP2C19 and 2D6 with IC50 values of 2.5, 3.6 and 0.5 μm, respectively. Our findings indicate that acetylshikonin may be a novel general P450 inhibitor, which could replace SKF‐525A.